Changes in the plasma aminogram of parenterally fed infants treated with dexamethasone for bronchopulmonary dysplasia. Issue 10 (October 1992) - Ng, P C; Brownlee, K G; Kelly, E J; Henderson, M J; Smith, M; Dear, P R
Abstract : A substantial increase in the plasma concentration of most amino acids was observed in 59 preterm infants with chronic lung disease soon after the initiation of dexamethasone therapy. The size of increase appeared to be dose related. This phenomenon is likely to be the result of steroid induced protein catabolism. Interestingly, neither phenylalanine nor tyrosine concentrations were significantly increased.